Evaluation of Oxidative-Stress Pathway and Recovery of Sudden Sensorineural Hearing Loss - Elias,Thaís Gomes Abrahão (2021)
Abstract Introduction Although the pathogenesis of sudden sensorineural hearing loss (SSNHL) has been discussed in the literature, many unclear points remain. Several authors have hypothesized that oxidative stress plays a role in the pathogenesis of noise-related hearing loss, as well as in drug- and aging-related hearing loss. Reactive oxygen species (ROS) may contribute to the pathogenesis of SSNHL in a similar way as in cases of ototoxicity, noise-induced hearing loss and presbyacusis. Objective The aim of the present study was to find potential peripheral biomarkers to show the levels of oxidative stress in samples of peripheral blood collected from SSNHL patients with and withouth metabolic disease. Methods In total, 80 consecutive patients with SSNHL were evaluated in the otolaryngology emergency room and outpatient clinic of a tertiary hospital between May 2017 and May 2019. All patients underwent detailed anamnesis, physical examination, audiometry, magnetic resonance imaging (MRI) of the inner ears, and blood tests for serum lipids and plasma activity of thiobarbituric acid reactive species (TBARS). Results No significant effect of malondialdehyde (MDA) activity was observed regarding the hearing recovery of patients who developed SSNHL. Conclusion We did not observe a significant correlation between the concentration of TBARs in the peripheral blood or the presence of arterial hypertension and the severity of the initial hearing loss or the prognosis of hearing recovery in patients with SSNHL. The concentration of TBARs in the peripheral blood may not adequately represent the abnormalities that occur in the intracoclear environment.